(E)-2-[(4-Chloro-phen-yl)Iminomethyl]-4-(Trifluoro-meth-oxy)Phenol - Tüfekçi, M.; Alpaslan, Y.B.; Macit, M.; Erdönmez, A. (Int Union Crystallography, 2009)
The title compound, C14H9ClF3NO 2, crystallizes in a phenol-imine tautomeric form, with a strong intra-molecular O- H⋯N hydrogen bond. The dihedral angle between the two benzene rings is 47.62 (9)°. In the crystal, mol-ecules are linked into chains along the c axis by C- H⋯O hydrogen bonds, and weak C- H⋯π inter-actions involving both benzene rings are also observed.